Calculation and Optimization of Plasma-Based Utilization Process of Inflammable Wastes after Reprocessing of Spent Nuclear Fuel of Closed Nuclear Cycle; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Karengin A. G. Aleksandr Grigorievich; Karengin A. A. Alexey Alexandrovich; Novoselov I. Yu. Ivan Yurievich; Tundeshev N. V. Nikolay Vladislavovich (Plasma, Microwave, Ion, Electron and Isotope Technologies, 2015)
Title screen